2000
DOI: 10.1111/j.1469-7998.2000.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of jaguars and pumas in Jalisco, Mexico

Abstract: Jaguars (Panthera onca) and pumas (Puma concolor) are sympatric over much of their geographic range in Mexico and South and Central America. We investigated diets of these felids in and around the Chamela-Cuixmala Biosphere Reserve in western Jalisco, Mexico. Diets were determined from scat analyses and documentation of prey cadavers. Relative biomass of each prey species consumed by pumas and jaguars was estimated from analysing 65 puma and 50 jaguar scats collected from 1995 to 1998. Both jaguars and pumas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 22 publications
(37 reference statements)
5
68
2
13
Order By: Relevance
“…: Emmons 1987, Olmos 1993, Aranda & Sánchez-Coedero 1996, Facure & Giaretta 1996, Nuñez et al 2000, Crawshaw & Quigley 2002, Leite & Galvão 2002. In our study small mammals were most commonly found in the diet of the Puma compared with other items.…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…: Emmons 1987, Olmos 1993, Aranda & Sánchez-Coedero 1996, Facure & Giaretta 1996, Nuñez et al 2000, Crawshaw & Quigley 2002, Leite & Galvão 2002. In our study small mammals were most commonly found in the diet of the Puma compared with other items.…”
Section: Dietmentioning
confidence: 99%
“…Puma concolor: the diet of Puma in the neotropics is composed mainly of medium to large sized mammals, including: Peccaries, Deers, Pacas, Coatis and Capybaras (Emmons 1987, Olmos 1993, Aranda & Sánchez-Coedero 1996, Facure & Giaretta 1996, Guix 1997, Taber et al 1997, Nuñez et al 2000, Crawshaw & Quigley 2002, Leite & Galvão 2002, although smaller prey, like small mammals, birds, reptiles, fish, invertebrates and fruits are also consumed (e.g. : Emmons 1987, Olmos 1993, Aranda & Sánchez-Coedero 1996, Facure & Giaretta 1996, Nuñez et al 2000, Crawshaw & Quigley 2002, Leite & Galvão 2002.…”
Section: Dietmentioning
confidence: 99%
“…Although the sampled species hold peculiar habitat preferences (Chinchila, 1997;Jácomo et al, 2004;Nuñez et al, 2000;Oliveira, 1998), recent studies show that animals may adapt to modifications in their original habitats (Morán-López et al, 2006;McDougall et al, 2006;Sánchez-Hernandéz et al, 2001;Tabeni et al, 2005). The present study indicates the registered carnivores use the habitats indistinctively in the study area.…”
Section: Discussionmentioning
confidence: 68%
“…Embora alguns autores apontem preferências de cada uma das espécies amostradas por determinados habitats (Chinchila, 1997;Jácomo et al, 2004;Nuñez et al, 2000;Oliveira, 1998) (Azevedo, 1996;Donadio et al,2001;Emmons, 1987;Franklin, et al,1999). Porém, espécies extremamente especialistas, como a P.…”
Section: Discussionunclassified
“…Com base nos itens encontrados em cada amostra foram calculadas: a porcentagem de ocorrência dos itens encontrados nas fezes (PO) e a frequência de ocorrência (FO) (RABINOWITZ & NOTTINGHAM, 1986;ACKERMAN et al, 1984;NUÑEZ et al, 2000). A freqüência de ocorrência indica se o item é mais ou menos comum na dieta, já a porcentagem de ocorrência indica a importância de cada item na dieta (MAEHR & BRADY, 1986 4 100 80 2 100 50 ---1 100 100 Aves ------------Répteis ------------Invertebrados ---1 50 25 1 100 100 ---Frutos ------------Material vegetal 1 25 20 1 50 25 ----- Os felinos, de modo geral, tendem a apresentar uma dieta mais carnívora (OLMOS, 1993;FACURE & GIARETTA, 1996), enquanto procionídeos e mustelídeos uma dieta onívora (p.ex.…”
Section: Análise Dos Dadosunclassified